Evolutionary algorithm approach for solving animal diet formulation - Abd Rahman, Rosshairy; Ramli, Razamin; Jamari, Zainoddin; Ku-Mahamud, Ku Ruhana (2015)
One of the pillars in animal farming industries is formulation of food for the animal, which is also known as diet formulation.However, the feed component in the aquaculture industry incurs the most expensive operational cost, and has drawn many studies regarding diet formulation.Hence, this study aims to solve animal diet formulation problem with ratio constraint using evolutionary algorithm approach.Actual data with 14 ingredients and 18 nutrients were taken into consideration.The result shows that evolutionary algorithm provides feasible solution in all runs. Experimentation on what-if scenario has proven that this evolutionary model is robust as it can adopt to changes in the parameter.